Cross-domain access control policy mapping mechanism for balancing interoperability and autonomy - Tianyi ZHU; Fenghua LI; Wei JIN; Yunchuan GUO; Liang FANG; Lin CHENG (Tongxin xuebao)
Cross-domain access control can improves interoperability but reduces intra-domain autonomy.To balance inter-domain interoperability and intra-domain autonomy,a cross-domain access control policy mapping to the problem of multi-objective integer optimization programming was formulated.Both the maximization of inter-domain interoperability and the minimization of intra-domain autonomy were taken as the objectives.Further,seven constraints were designed to prevent typical cross-domain conflicts.To solve the optimization problem,a constrained NSGA-III algorithm was proposed.The experimental results show that the proposed algorithm can quickly converge and accurately find the policy mapping even in the large-scale datasets.